Facilitating cooperation during times of chaos: spontaneous orders and muddling through in Malinau - Wollenberg, Eva Karoline; Iwan, R.; Limberg, G.; Moeliono, M.; Rhee, S.; Sudana, M. (2007)
Adaptive management has become increasingly common where natural resource managers face complex and uncertain conditions. The collaboration required among managers and others to do adaptive management, however, is not always easy to achieve. We describe efforts to work with villagers and government officials in Malinau, East Kalimantan Indonesia, where a weak, uncertain institutional setting and complex shifting political landscape made formal cooperation among these groups for forest management problematic. Through successive trials, the team learned instead to work with and enhance a “spontaneous order” of cooperation using four tactics: (1) continuous physical presence, (2) regular contact with the people who advised and were close to major decision makers, (3) maintenance of multiple programs to fit the needs of different interest groups, and (4) hyperflexibility in resource allocation and schedules.